SISTEM E-SAMSAT SUMUT BERMARTABAT : SEBUAH INOVASI UNTUK MENINGKATKAN PELAYANAN PUBLIK - Pohan, Syafruddin; Ivana, Rima; Kurniasih, Fenny (Universitas Djuanda, 2023)
Technological advances are growing rapidly and have reached every aspect of human life. This research aims to investigate how the E-Samsat Sumut Bermartabat system acts as an innovation to improve public services for residents in the province of North Sumatra. This research uses a descriptive method with a qualitative approach, where data is collected through literature review from books and scientific journals. From the literature, it was revealed that the use of the E-Samsat Sumut Bermartabat application has advantages and disadvantages. One of the advantages is that the PKB payment process becomes easier, faster, and more accurate. Meanwhile, one of the weaknesses is the unevenness of the internet network and the lack of socialization among the community regarding procedures and how to use this application, so not all North Sumatra residents have the ability to use the application to pay taxes.